Dynamics of Social Engagement Illustrated by Area Based Development Research Journal - Sirisathitkul, Chitnarong; Sirisathitkul, Yaowarat (Area Based Development Research Journal, 2019)
Area Based Research and Development Journal, commissioned by TSSR, has been published bi-monthly in its 9th-11th year. From October 2016 to December 2019, 115 articles out of 243 submissions has been accepted for publication. These contributions reflect the diversity of area-based collaborative research and social engagement, demonstrating the linkage between university and local community. Classified by the affiliation of corresponding authors, 65 establishments include university, private institution , college and hospital. Furthermore, the articles published in the journal exhibit a variety in academic disciplines and regions. In terms of geographical diversity, the highest number of works (36) were carried out in the south of Thailand followed by the northern (28), central (23) and northeastern (19) regions. In terms of disciplines, the published papers are classified into 1) Agriculture and product developments (36 articles), 2) Tourism and creative economy (23 articles), 3) Community health (15 articles), 4) Research management (8 articles), 5) Culture and local wisdom (8 articles), 6) Education (7 articles), 7) Social mechanism and community management (7 articles), 8) Rural technology and inventions (6 articles), 9) Participatory in natural resource and environmental management (5 articles). For the research management, the articles are lessons and best practices written by executives, research administrators and reviewers. Such works are not often available as journal articles, giving rise to the uniqueness of Area Based Research and Development Journal. Currently, the journal is processed on the ThaiJo2 platform and indexed in tier 1 of Thai-Journal Citation Index (TCI). Publications of area-based collaborative research and social engagement in the journal can lead to the promotion of academic position, in both traditional and socially engaged scholarship tracks.